Modifications in ornithine decarboxylase and diamine oxidase in small bowel mucosa of starved and refed rats. (1987) - D'Agostino, L; Daniele, B; Pignata, S; Barone, M V; D'Argenio, G; Mazzacca, G
Abstract : Starvation followed by refeeding, which provides a model of intestinal adaptation characterised by proliferative and biochemical changes, was used to clarify the biological roles of ornithine decarboxylase (ODC) and diamine oxidase (DAO)--enzymes involved in polyamines metabolism. Ornithine decarboxylase and DAO were assayed in the proximal and distal small bowel mucosa of 55 rats, starved for four days and then refed. Rats (five per day) were killed after four days' starvation and at days 1, 2, 3, 4, 5, 6, 7, 8, 10 and 12 of refeeding. ODC, whose specific activity was similar in both intestinal segments, almost disappeared after starvation and showed a biphasic response during refeeding. High values were found on day 3 of refeeding in the proximal, and on day 4 in the distal small bowel; thereafter, they decreased gradually to be followed by a further significant increase during the last two days of the experiment. Diamine oxidase specific activity increased after starvation despite a very low total DAO activity in both intestinal segments. Refeeding induced a gradual recovery of DAO total activity. Diamine oxidase specific activity also reverted gradually to control values after five days of refeeding. These data confirm the prominence of ODC in the replication processes and suggest that intestinal DAO may not play a major role in enterocyte replication.